Students’ Perceptions of TikTok Content Creation as a Medium to Support Speaking and Pronunciation Skills - Yuricho Dafa Mahendra; Dzul Rachman; Ade Ismail Ramadhan Hamid (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study investigates the effectiveness of using TikTok as a learning medium to improve students’ pronunciation and speaking skills. The increasing popularity of TikTok among students offers opportunities to integrate short-form video content into English language learning; however, empirical evidence on its instructional impact remains limited. This study employed a quantitative pre-experimental design using a one-group pretest–posttest approach. The participants were undergraduate students from an English education program who were selected through purposive sampling. Data were collected using pronunciation and speaking performance tests administered before and after the treatment. The treatment was implemented through structured learning activities using selected TikTok videos that modeled authentic pronunciation, intonation, and spoken interaction. Students practiced imitating pronunciation, producing short spoken responses, and recording their performances. The data were analyzed using descriptive statistics and paired-sample statistical tests to examine differences between pretest and posttest scores. The results indicate a significant improvement in both pronunciation and speaking performance after the implementation of TikTok-based instruction. Students demonstrated clearer articulation, improved fluency, and increased confidence in oral production. The findings suggest that TikTok can serve as an engaging supplementary medium to support pronunciation practice and speaking development when guided by structured instructional activities. This study contributes practical insights for language teachers seeking to integrate digital media into speaking instruction and highlights the need for further research using larger samples and comparative designs.